Concise machinery for monitoring ubiquitination activities using novel artificial RING fingers - Miyamoto, Kazuhide (Protein Sci, 2018)
Protein ubiquitination is involved in many cellular processes, such as protein degradation, DNA repair, and signal transduction pathways. Ubiquitin‐conjugating (E2) enzymes of the ubiquitination pathway are associated with various cancers, such as leukemia, lung cancer, and gastric cancer. However, to date, detection of E2 activities is not practicable for capturing the pathological conditions of cancers due to complications related to the enzymatic cascade reaction. To overcome this hurdle, we have recently investigated a novel strategy for measuring E2 activities. Artificial RING fingers (ARFs) were developed to conveniently detect E2 activities during the ubiquitination reaction. ARFs were created by grafting the active sites of ubiquitin‐ligating (E3) enzymes onto amino acid sequences with 38 residues. The grafting design downsized E3s to small molecules (ARFs). Such an ARF is a multifunctional molecule that possesses specific E2‐binding capabilities and ubiquitinates itself without a substrate. In this review, we discuss the major findings from recent investigations on a new molecular design for ARFs and their simplified detection system for E2 activities. The use of the ARF allowed us to monitor E2 activities using acute promyelocytic leukemia (APL)‐derived cells following treatment with the anticancer drug bortezomib. The molecular design of ARFs is extremely simple and convenient, and thus, may be a powerful tool for protein engineering. The ARF methodology may reveal a new screening method of E2s that will contribute to diagnostic techniques for cancers.